Progestins in the symptomatic management of endometriosis: a meta-analysis on their effectiveness and safety - Jon-Benay Mitchell; Sarentha Chetty; Fatima Kathrada (BMC, 2022)
Abstract Background Endometriosis is a complex chronic disease that affects approximately 10% of women of reproductive age worldwide and commonly presents with pelvic pain and infertility. Method & outcome measures A systematic review of the literature was carried out using the databases Pubmed, Scopus, Cochrane and ClinicalTrials.gov in women with a confirmed laparoscopic diagnosis of endometriosis receiving progestins to determine a reduction in pain symptoms and the occurrence of adverse effects. Results Eighteen studies were included in the meta-analysis. Progestins improved painful symptoms compared to placebo (SMD = −0.61, 95% CI (−0.77, −0.45), P < 0.00001) with no comparable differences between the type of progestin. After median study durations of 6-12 months, the median discontinuation rate due to adverse effects was 0.3% (range: 0 − 37.1%) with mild adverse effects reported. Conclusion The meta-analysis revealed that pain improvement significantly increased with the use of progestins with low adverse effects. Systematic Review Registration PROSPERO CRD42021285026.